EFFECT OF ADMINISTRATIVE REFORM AND TAXPAYER SATISFACTION ON TAXPAYER COMPLIANCE AS RECORDED BY TAX OFFICES OF MAJALAYA BANDUNG - Ira Diah Anggraeni; Trisandi Eka Putri; Asri Suangga (Journal of Taxation Analysis and Review, 2019)
The Modernization of Tax Administration assist taxpayers in making their tax obligations. Taxpayers are expected to be satisfied with The Modernization of Tax Administration of existing so be abiding taxpayers in their tax obligations. The purpose of this research is to know the influence of tax administration modernization (X1) on taxpayer satisfaction (X2), to know the influence of tax administration modernization (X1) taxpayer compliance (Y), and taxpayer satisfaction (X2) to taxpayer Compliance ), And to know the influence of Modernization of tax administration (X1) to Compliance taxpayer (Y) through Taxpayer Satisfaction (X2). This study uses nonprobability sampling method with the number of samples of 100 respondents from taxpayers registered on KPP Pratama Majalaya Bandung. Data obtained from this research is primary data through questionnaire in the form of interval scale with analysis method using path analysis and using lisrel statistic program and tested in the form of validity test, reliability test, t test, and model fit test. The results of the analysis obtained the first substructure equation X2 = 0.731X1 + 0.465e1 and the second substructure equation Y = 0.307X2 + 0.843X1 + 0.860e2 Based on the results of t test says that the modernization of tax administration (X1) has a positive and significant impact on Compulsory Satisfaction tax (X2) and Modernization of tax administration (X1) have positive and insignificant effect on Taxpayer's Compliance (Y), Taxpayer's satisfaction (X2) have positive and significant influence to taxpayer Compliance (Y) and Modernization of tax administration have positive indirect effect against Taxpayer Compliance (Y) through Taxpayer Satisfaction (X2). The model fit test result is the accepted model.